Canalization of Ethnic Politics in Makassar - Sjaf, Sofyan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTLiberal democracy in the multicultural society provides practical consequences for the existence of ethnic political practices in local politic arena. This research aimedto found the canalization of ethnic politic in Makassar by using qualitative research method and actor-structural perspective, it emphasize on subjectivism, objectivism, and historical perspective.The units of analysis in this study were various actors who come from different ethnic backgrounds (Bugis, Makassar, Toraja, Mandar, and Chinese descent) in the city of Makassar, South Sulawesi. Data was collected by researchers through in-depth interviews, structured interviews, and Focus Group Discussion (FGD) with people from different backgrounds such as politicians, bureaucracy, academia, and NGO activists.Although the ethnic groups in Makassar have always shared the common value system, inter-ethnic relations are determined by three factors; the history of ethnicity, ethnic demographic structure, and dynamics of local politics based on ethnic. The three factors have various implications to the control of political and economic structure in the realm of ethnic politic. Thus, the result performed that is the pattern of political dynasty becomes an inevitable necessity.Keywords: Canalization, ethnic politic, Makassar, desentralizationABSTRAKPilihan demokrasi liberatif dalam masyarakat multikulturalisme memberikan konsekuensi hadirnya praktik-praktik politik etnik dalam arena politik lokal. Penelitian yang bertujuan menemukan pola kanalisasi politik etnik di Makassar ini menggunakan metode kualitatif berperspektif aktor-struktur dengan sifat penelitian subyektivisme, obyektivisme, dan historis. Unit analisis penelitian adalah aktor yang berasal dari latar belakang etnik berbeda (Bugis, Makassar, Toraja, Mandar, dan Cina) yang berdomisili di Makassar. Pengambilan data dilakukan dengan teknik wawancara mendalam, wawancara terstruktur, dan Focus Group Discussion (FGD) beragam profesi (politisi, birokrasi, akademisi, dan aktivis NGO). Terjadi pembauran kelompok etnik di Makassar dan siri’ sebagai nilai-nilai bersama yang diakui etnik Bugis maupun Makassar, namun relasi antar etnisitas di arena politik lokal ditentukan tiga faktor, yaitu sejarah etnisitas, struktur demografi etnik, dan dinamika politik lokal berbasis etnik. Selanjutnya ketiga faktor tersebut, berimplikasi terhadap penguasaan struktur politik dan ekonomi dalam kerangka politik etnik. Alhasil, pola kedinastian di arena politik lokal menjadi keniscayaan yang tidakterhindarkan.Kata kunci: Kanalisasi, politik etnik, Makassar, desentralisasi